BOOK REVIEW: Demartini P., Marchegiani L., Marchiori M., and Schiuma G., Cultural initiatives for sustainable development: management, participation and entrepreneurship in the cultural and creative sector, Springer, 2021. - Cipriano, Maria Antonietta (Piccola Impresa / Small Business, 2023)
The book offers an overview of innovative sources, dimensions of expertise for supporting creative and cultural organisations and initiatives. Authors highlighted the importance of cultural heritage, participatory approaches, and entrepreneurship in the cultural and creative sector with a further analysis on sustainable development. In accordance with cultural and creative entrepreneurship, the book provides an original outlook of cultural enterprises, offering some evidence from an entrepreneurial ecosystem perspective. Hence, the authors offer a map to better analyse the debate on the sustainable development linked to cultural heritage: (1) the levels of analysis (micro, meso, macro); (2) the four domains in which the sustainability concept unfolds (cultural, social, economic, and environmental) according to the Hangzhou Declaration (2013); and (3) the regenerative processes of cultural initiatives that are consistent with the sustainability perspective (management, participation, entrepreneurship). Conclusively, the four Editors propose main themes that should be further explored to deepen the debate about cultural initiatives and sustainability.